Impact of drip irrigation amount on growth and water use efficiency of spring wheat in Northern Xinjiang - LI Peiwen; ZHANG Chunyan; WEI Changzhou; LI Qiuyue; ZHANG Yidan; WANG Juan (Guan'gai paishui xuebao)
【Objective】 Spring wheat is an important cereal crop in Northern Xinjiang, where limited precipitation during the growing season makes irrigation essential for its successful production. This paper investigates the effect of irrigation amount on its growth traits and final yield, in attempts to identify an optimal irrigation schedule for spring wheat in this region. 【Method】 The field plot experiments were conducted using the high-yielding varieties ‘Xinchun 37’ and ‘Xinchun 44’. Each variety was subjected to four irrigation treatments: 4 500 m3/hm2 (W1, resulting in severe drought), 5 250 m3/hm2 (W2, resulting in moderate drought), 6 000 m3/hm2 (W3, normal irrigation), and 6 750 m3/hm2(W4, excessive irrigation). For each irrigation treatment, we measured the growth traits, water use efficiency, and grain yield of the two crops. 【Result】 Soil water content in the 0-60 cm layer increased with the irrigation amount, with water in the 0-20 cm soil layer showing the most significant fluctuation. With the increase in irrigation amount, plant height and dry matter accumulation of both varieties increased initially, followed by a decline. It was also found that the grain-filling period of Xinchun 37 was longer than that of Xinchun 44. Compared to W4, W3 increased the water use efficiency of Xinchun 37 and Xinchun 44 by 30.00% and 15.45%, respectively, the irrigation water use efficiency by 33.91% and 19.85%, respectively. Compared to all other treatments, W3 increased the grain yield of Xinchun 37 by 14.45%-38.24%, while compared to W1 and W2, it increased the grain yield of Xinchun 44 by 25.76% and 14.45%, respectively. 【Conclusion】 Regression analysis shows that the optimal irrigation amount for Xinchun 37 and Xinchun 44 was 5 875.83 m3/hm2 and 5 967.67 m3/hm2, respectively, in the studied region.